Automation requirements engineering using machine learning - Abid, Md.Mehedy Hasan; Tanna, Rubaya Neshat; Noyon, Mahbubur Rahman; Masud, Jahidul Hasan; Akter, Tahmina (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.